Curso temporal da função e marcadores de dano tecidual musculares após partida de rugby - SILVA, Rodrigo Barboza da (2013)
Rugby union match requires performing various high intensity motor actions and contact, resulting in tissue damage and reduced muscle function for hours or even days after the match. The knowledge of the recovery process is important for the physical reestablishment and training periodization, because when an individual is not recovered he is more prone to injury and have athletic performance below expected. The aim of this study was to evaluate the recovery time of blood markers of tissue damage and markers of muscle function, after rugby match, using specific rugby tests. The study included 14 amateur athletes from a rugby union team. Blood creatine kinase and lactate dehydrogenase (CK, LDH), acceleration, speed and agility time (T10, T30, TL) were measured at rest (Pre) and five other moments (0, 24, 48, 72, 96 h) after a game of Rugby State Championship. To verify temporal response of variables, One Way Anova test was used, and when necessary the post-hoc Tukey test (p <0.05). To verify the correlation between muscle damage and performance aspects, the Pearson correlation test was used. CK increased by 305.8% 24 h post-match (P <0.05) compared to the pre-game, normalizing at 72 h post-game. LDH increased 33.6% 0 h post-match (P <0.05), returning to pre-match values in 24 h. T10 increased 11.4% 0 h post-match (P <0.05), after 72 h showed a tendency to return to pre-match values. T30 increased 6% 0 h post-match (P <0.05) and returned to baseline 24 h post-match. TL increased by 16.1% 24 h post-game (P <0.05) and remained elevated for at least 96h post-match. There was no correlation between biochemical and performance variables on any of the evaluated times, suggesting that the decline in muscle function is not only due to muscle damage. The results of this study suggest that a game of rugby union causes significant tissue damage on players, decreases the performance of the assessed physical tests and the investigated physical abilities have different recovery times.